Pertumbuhan Widelia (Wedelia trilobata (L) Hitchc) pada Tingkat Naungan Berbeda di Jalur Hijau Kota Yogyakarta - Dewi Maimunah; Siti Nurul Rofiqo Irwan; Didik Indradewa (Jurnal Ilmu Pertanian Indonesia, 2020)
Widelia plant (Wedelia trilobata (L) Hitchc) is a spreading herb from the Asterase family that potentially can be used as a ground cover in the roadside greenery because this plant has a faster growing rate and has aesthetic values in both leaves and flowers. The aim of this study was to observe the microclimate of the roadside greenery and the vegetative growth of widelia at three levels of the tree canopy shades in the collector and local roads of Yogyakarta City. The experiment was carried out using an inter-site design (oversite) consisting of two factors, namely road factors (collector roads and local roads) and levels of shade canopy (full > 50%, moderate 20–50% and no shade 0%). The results of the analysis of variance did not show any significant differences on the microclimate and widelia growth parameters on the collector or local roads. The wind speed, noise, and number of vehicles on the collector road showed the higher number compared to those on the local road. The results of analysis of variance in the three levels of tree canopy shade also showed significant differences in microclimate and widelia growth parameters. The lowest light intensity, air temperature, humidity, soil temperature, soil moisture, stolon length, number of leaves, number of shoots, number of segments, and dry weight plants were found in full shade level (> 50%). All observation variables did not show any significant interaction effect between the two types of roads and the three levels of tree shades. Keywords: canopy shade, microclimate, roadside greenery, widelia (Wedelia trilobata (L) Hitchc), Yogyakarta